TOXICITY OF ETHANOL EXTRACT FROM CHINESE LEUCAENA LEAF (Leucaena leucocephala) USING THE ARTEMIA SALINA BIOASSAY METHOD - Kony Putriani; Wahyu Margi Sidoretno; Ayatu Fahmi (LPPM Universitas Abdurrab, 2025)
Chinese petai (Laucaena leucocephala) is a plant from the Fabaceae family. This plant contains several active compounds, including alkaloids, flavonoids, steroids, saponins, and tannins, making it a potential herbal medicine in Indonesia. This research aims to determine the toxicity of petai cina leaf extract using the Brine Shrimp Lethality Test (BSLT) method. The extraction process of Chinese petai leaves uses 96% ethanol solvent with the maceration method, then a phytochemical screening is carried out, which shows that the Chinese Petai leaf samples contain alkaloids, flavonoids, steroids, saponins, and tannins. Testing the toxicity of the ethanol extract of petai cina leaves on Artemia salina Leach larvae was divided into 5 test groups, namely 4 treatment groups (concentration 250 ppm, 500 ppm, 750 ppm, and 1000 ppm) and 1 control or comparison group (seawater). Each concentration was made in 3 vials containing 10 Artemia salina Leach larvae. Observations were made by looking at the death of Artemia salina Leach larvae after 24 hours of treatment. The research results can be seen through probit analysis by calculating the LC50 value. The LC50 value of the ethanol extract of petai cina leaves was 31.57342 µg/ml. This shows that the ethanol extract of petai cina leaves has a toxic effect on Artemia salina Leach larvae because the LC50 value is <1000 ppm.